1981
DOI: 10.1136/thx.36.9.683
|View full text |Cite
|
Sign up to set email alerts
|

Is cough as effective as chest physiotherapy in the removal of excessive tracheobronchial secretions?

Abstract: The relative value of chest physiotherapy (including cough) and cough alone for the removal of excessive tracheobronchial secretions has been assessed in six patients with stable chronic obstructive lung disease. After labelling with inhaled radioactive tracer particles, clearance of secretions from selected central and peripheral lung regions was followed with a gamma camera linked to a computer. Cough alone and chest physiotherapy (including cough) were equally effective in the enhancement of central lung cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 15 publications
1
30
1
3
Order By: Relevance
“…5 Both that study and ours showed the mean frequencies of vibration lower than those in other studies with recorded frequencies of 10 to 16 Hz. 6,7,9 The seven physiotherapists in our study who performed shaking instead of vibration (in at least one of the three conditions) applied frequencies outside those demonstrated in previous literature of 6.3 Hz 9 and 2 Hz 6,7 (see Table 1). Those studies evaluated vibration, shaking, or both techniques, performed on a black anaesthetic bag 6 or on intubated and ventilated sheep; 9 one study failed to indicate the method of measurement used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Both that study and ours showed the mean frequencies of vibration lower than those in other studies with recorded frequencies of 10 to 16 Hz. 6,7,9 The seven physiotherapists in our study who performed shaking instead of vibration (in at least one of the three conditions) applied frequencies outside those demonstrated in previous literature of 6.3 Hz 9 and 2 Hz 6,7 (see Table 1). Those studies evaluated vibration, shaking, or both techniques, performed on a black anaesthetic bag 6 or on intubated and ventilated sheep; 9 one study failed to indicate the method of measurement used.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9 The seven physiotherapists in our study who performed shaking instead of vibration (in at least one of the three conditions) applied frequencies outside those demonstrated in previous literature of 6.3 Hz 9 and 2 Hz 6,7 (see Table 1). Those studies evaluated vibration, shaking, or both techniques, performed on a black anaesthetic bag 6 or on intubated and ventilated sheep; 9 one study failed to indicate the method of measurement used. 7 It is not clear why these studies demonstrated differences in the frequencies of vibration or shaking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regions of interest (ROI) were drawn by a radiologist to obtain counts in each lung region on each image. Division of the lung image into central, intermediate and peripheral zones was performed according to description of Bateman et al 16) The data from the right lung were analyzed. All counts were corrected for radionuclide decay and background radioactivity.…”
Section: Methodsmentioning
confidence: 99%